A tributação indutora como mecanismo de efetivação dos direitos sociais: análise da extrafiscalidade no direito à saúde - Alcântara, Carlos Wendel Peixoto de (2019)
The paper deals with the applicability of tax law in the implementation of the fundamental right to health. It deals with the characteristics and functions of taxation in the legal system in the tax, parafiscal and especially extrafiscal aspects, demonstrating its importance in inducing behavior, as well as its constitutionality, despite the fact that it provides and establishes an unequal treatment of taxpayers. It traces the succinct historical evolution of social relations and tributes, from the most primitive communities to the present day. It clarifies the State's duty, whether from an internationalist or internal perspective, regarding the need to provide quality health services to all, as well as the inapplicability of the theory of the reserve of the possible to basic fundamental rights and closely related to the dignity of the person human. It presents the social right to health under the most preventive prism to the detriment of the curative, without, however, forgetting the importance of the latter for the quality of life of the citizens. It exposes the basic relationship of health with the free and full exercise of other rights arising from the legal system of the country, especially when health is understood in a more global way, not referring only to the healthy organism and disease free. It shows some practical postures that can be adopted by the State in guaranteeing the right to health, which would result in the efficiency of the public health service and reduction of expenses, notably related to the healthy environment, correct and balanced nutrition, among others. In order to do so, it proposes the implementation of an integrated tax policy at the federal, state, district and municipal levels, with the purpose of giving priority to those practices that improve the quality of life of individuals, to the detriment of those that harm, through taxation. However, it should be borne in mind that the use of such mechanisms may lead to unlawful distortion, which undermines the central objective of improving the health of persons for the personal benefit of certain natural or legal persons. As a proposed solution to this problem, there is a need for effective and effective social control mechanisms, in order to control the extrafiscal positions handcuffed. The present dissertation adopts the historical, evolutionary, dialectical scientific methods.